Luteolin and apigenin activate the Oct‐4/Sox2 signal via NFATc1 in human periodontal ligament cells. (9th August 2016) - Liu, Lu; Peng, Zhengjun; Huang, Haoquan; Xu, Zhezhen; Wei, Xi
Abstract: Identifying small molecules to activate the Oct‐4/Sox2‐derived pluripotency network represents a hopeful and safe method to pluripotency without genetic manipulation. Luteolin and apigenin, two major bioactive flavonoids, enhance reprogramming efficiency and increase expression of Oct‐4/Sox2/c‐Myc, albeit the detailed mechanism regulating pluripotency in dental‐derived cells remains unknown. In the present study, to elucidate the effect of luteolin/apigenin on pluripotency of periodontal ligament cells (PDLCs) through interaction with downstream signals, we examined cell cycle, proliferation, apoptosis, expression of Oct‐4/Sox2/c‐Myc, and multilineage differentiation of PDLCs with luteolin/apigenin treatment. Moreover, we profiled the differentially expressed pluripotency genes by PCR arrays. Our results demonstrated that luteolin/apigenin restrained cell proliferation, increased apoptosis, and arrested PDLCs in G2/M and S phase. Luteolin and apigenin activated expression of Oct‐4, Sox2, and c‐Myc in a time‐ and dose‐dependent pattern, and repressed lineage‐specific differentiation. PCR arrays profiled multiple signals in PDLCs with luteolin/apigenin treatment, among which NFATc1 was the major upregulated gene. Notably, blocking of the NFATc1 signal with INCA‐6 significantly decreased mRNA and protein expression of Oct‐4, Sox2, and c‐Myc in PDLCs with luteolin/apigenin treatment, indicating that NFATc1 may act as an upstream modulator of Oct‐4/Sox2 signal. Taken together, this study showed that luteolin and apigenin effectively maintain pluripotency of PDLCs through activation of Oct‐4/Sox2 signal via NFATc1.